In vitro Anti-Toxoplasma gondii Activity of Root Extract/Fractions of Eurycoma longifolia Jack - Kavitha Nowroji; Noordin Rahmah; Chan Kit-Lam; Sasidharan Sreenivasan (BMC, 2012)
Abstract Background Toxoplasma gondii infection causes toxoplasmosis, an infectious disease with worldwide prevalence. The limited efficiency of drugs against this infection, their side effects and the potential appearance of resistant strains make the search of novel drugs an essential need. We examined Eurycoma longifolia root extract and fractions as potential sources of new compounds with high activity and low toxicity. The main goal of this study was to investigate the anti-T. gondii activity of crude extract (TACME) and four fractions (TAF 273, TAF 355, TAF 191 and TAF 401) from E. longifolia, with clindamycin as the positive control. Methods In vitro toxoplasmacidal evaluation was performed using Vero cells as host for T. gondii. Light microscopy technique was used to study in situ antiparasitic activity. Results Significant anti-T. gondii activity was observed with clindamycin (EC50 = 0.016 μg/ml), follow by TAF 355 (EC50 = 0.369 μg/ml) and TAF 401 (EC50 = 0.882 μg/ml). Light microscopy revealed that most Vero cells were infected after 3 h of exposure to T. gondii. After 36 h of exposure to the E. longifolia fraction, the host Vero cells showed no visible intracellular parasite and no remarkable morphological changes. Conclusions Our study demonstrated that TAF 355 and TAF401 fractions may be the sources of new anti-T. gondii compounds.